Labeling monocytes with gold nanoparticles to track their recruitment in atherosclerosis with computed tomography. (May 2016) - Chhour, Peter; Naha, Pratap C.; O'Neill, Sean M.; Litt, Harold I.; Reilly, Muredach P.; Ferrari, Victor A.; Cormode, David P.
Abstract: Monocytes are actively recruited from the circulation into developing atherosclerotic plaques. In the plaque, monocytes differentiate into macrophages and eventually form foam cells. Continued accumulation of foam cells can lead to plaque rupture and subsequent myocardial infarction. X-ray computed tomography (CT) is the best modality to image the coronary arteries non-invasively, therefore we have sought to track the accumulation of monocytes into atherosclerotic plaques using CT. Gold nanoparticles were synthesized and stabilized with a variety of ligands. Select formulations were incubated with an immortalized monocyte cell line in vitro and evaluated for cytotoxicity, effects on cytokine release, and cell uptake. These data identified a lead formulation, 11-MUDA capped gold nanoparticles, to test for labeling primary monocytes. The formulation did not the affect the viability or cytokine release of primary monocytes and was highly taken up by these cells. Gold labeled primary monocytes were injected into apolipoprotein E deficient mice kept on Western diet for 10 weeks. Imaging was done with a microCT scanner. A significant increase in attenuation was measured in the aorta of mice receiving the gold labeled cells as compared to control animals. Following the experiment, the biodistribution of gold was evaluated in major organs. Additionally, plaques were sectioned and examined with electron microscopy. The results showed that gold nanoparticles were present inside monocytes located within plaques. This study demonstrates the feasibility of using gold nanoparticles as effective cell labeling contrast agents for non-invasive imaging of monocyte accumulation within plaques with CT.